Achados na Caixa de Pandora: opções de superação do analfabetismo moral na escola - Mesquita, Regina Elizabeth Mattos Dourado de (2010)
The present study investigates how school is a contribution to the setting of childhood morality, as a potentially suitable space, and how school agents (managers, teachers, technicians) undertake such elaboration. It also presents the strategies applied by schools in order to favour the prevailing of a positive moral atmosphere, enhancer of moral activities which lead to respect, acceptance and solidarity. The research was developed at a municipal public school in Fortaleza, in one of the most violent neighborhoods in town, and the main subjects were two first grade elementary school female teachers, the school manager and fifty-two of their students. It followed the ethrographic investigation approach, and adopted the instruments of observation, debriefing interviews, life story, questionnaire and analysis of the institution’s official files. The main theory basing authors are Piaget (1998), Kohlberg (1975, 1978), Yves de la Taille (2000, 2002, 2006, 2009) and Araújo (2002, 2003, 2004). It identified a positive moral atmosphere at the school, unfolded along five years by strategies such as welcome, conflict mediation and artistic activities, all promoted by the institution, referring the VIVE (living values in education) Program associated to the school’s political pedagogic project, through transverse curriculum behavior. Some analysis outcomes are highlighted: 1 – non-involvement of great part of the teachers in the political pedagogic project with moral focus; 2 – the morality focused work being centralized in the school manager and three teachers who attended courses at the VIVE Program; 3 – absence of a result control to the morality focused social activities, which would guarantee an intentional and systematic approach form teachers’ didactic pedagogic point of view; 4 – children’s passive attitude on their own expansion, in spite of the curricular systematization of morality focused activities; 5 – active caution and watch attitudes, although sparse, as conduct line of school adults upon children. The study offers elements for the reflection on the importance of school as a favorable space to child morality. Moreover, it presents means of working the moral issue integrated to the school conventional curriculum, by its transverse behavior – not artificial, moralizing or orthodox.